Application of the Vigenere Cipher Algorithm in Database Security of Employee Performance Values at the South Bengkulu Regency Education and Culture Office - Andita, Yolanda Tri; Aspriyono, Hari; Rohmawan , Eko Prasetiyo (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
Security and confidentiality of data or information is an important aspect of data or information. The problem of security and confidentiality of computer data is something that is important in this information age, especially for the South Bengkulu Regency Education and Culture Office. Various ways were done to protect the data or information. Encryption is used to change the original text to unreadable text. Decryption is used to convert unreadable text to original text. Database security application for employee performance values ​​at the South Bengkulu Regency Education and Culture Office was made using the Visual Basic .Net Programming Language and SQL Server Database. In this application, one of the classic cryptographic algorithms has been implemented, namely the Vigenere Cipher Algorithm to secure the contents of the database record, so that what is stored in the database record has been randomized by the algorithm. Based on the encryption results generated by the Vigenere Cipher Algorithm, it is only able to randomize plaintext containing alphabets, and is unable to randomize plaintext containing numeric.